Development of a nomogram for overall survival prediction in primary upper lobe lung cancer patients: A SEER population-based analysis - Wenze Yu; Lu Long; Qizhuo Hou; Bin Yi (PLoS ONE, 2025)
Background The upper lobe is the most common site of primary lung cancer, however, very few reports focus on its prognosis. This study aims to identify prognostic factors of lung cancer in the upper lobe, as well as to establish an effective nomogram for individualized overall survival (OS) prediction. Methods Patients diagnosed with lung cancer were collected from the Surveillance, Epidemiology, and End Results Program (SEER) database for the period of 2010–2017,as recorder in the 2021 SEER database release. The demographic characteristics and OS differed in the primary sites of the upper, middle and lower lobes were drawn. The primary upper lobe lung cancer patients were further stratified by the risk indicators including Mets at DX-bone, stage, histology, grade and sex; and their OS differences in stratification were compared by the Kaplan-Meier method and the Log-Rank test. The univariate and the multivariate Cox regression were employed to determine the independent prognostic factors for the primary upper lobe lung cancer and to build a nomogram model for its OS prediction. Results Depending on the different primary sites of lung cancer occurrence, all the collected patients were divided into three groups of the upper lobe (30295 individuals), the middle lobe (2801 individuals) and the lower lobe (16757 individuals), where the upper lobe group gained our attention with the largest population and an overwhelmingly low OS compared to the middle lobe group (P <0.0001). With the results of the univariate and multivariate Cox regression model analyses, age, sex, grade, histology type, stage, regional lymph nodes removed, bone metastasis and liver metastasis were selected as the prognostic factors and a prediction nomogram model was built. The calibration curves showed no significant bias from the reference line and the concordance index between the survival nomogram prediction and the actual outcome for 2-year and 3-year OS was 0.761 (95% CI, 0.757–0.765). The time-dependent receiver operating characteristic curves showed that the areas under curve for 2-year and 3-year OS were 0.840 and 0.836, respectively. Conclusion A novel nomogram was established which achieved good performance in predicting the probability of OS in the primary upper lobe lung cancer, indicating its potential value in individualized prediction of the clinical outcome in these patients.